2020
DOI: 10.1186/s13550-020-00660-y
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG uptake of bone marrow on PET/CT for predicting distant recurrence in breast cancer patients after surgical resection

Abstract: Background: The objective of this study was to investigate the prognostic value of 2-Deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) uptake of bone marrow (BM) and metabolic parameters of primary tumor on positron emission tomography/computed tomography (PET/CT) for predicting distant recurrence in patients with breast cancer. Methods: Pretreatment [ 18 F]FDG PET/CT images of 345 breast cancer patients were retrospectively evaluated. Maximum standardized uptake value, metabolic tumor volume, and total lesion glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The spleen-to-liver ratio of SUV (SLR) was calculated by dividing the spleen SUVmean by the liver SUVmean, and the bone marrow-to-liver ratio of the SUV (BLR) was calculated by dividing the bone marrow SUVmean by the liver SUVmean, similarly to previous reports. 28 30 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%
“…The spleen-to-liver ratio of SUV (SLR) was calculated by dividing the spleen SUVmean by the liver SUVmean, and the bone marrow-to-liver ratio of the SUV (BLR) was calculated by dividing the bone marrow SUVmean by the liver SUVmean, similarly to previous reports. 28 30 , 34 , 35 …”
Section: Methodsmentioning
confidence: 99%
“…Demonstration that lymphoid tissue glucose metabolism is an imaging biomarker correlated with RFS in breast cancer is an interesting finding, consistent with data published in the literature. In a recent study, Lee et al explored the association between RFS or DRFS (systemic control) and PET biomarkers including bone marrow metabolism (BLR) in 345 patients with invasive ductal (89%) or lobular (11%) breast carcinoma treated by upfront surgery prior to adjuvant therapy [24]. They confirmed that metabolic tumor volume and noninvasive measurement of glucose metabolism on nontumoral lymphoid tissues can both be used to predict recurrence, especially the onset of metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Nontumoral lymphoid tissues. Liver, spleen, and BM SUVmax values were computed with the same methodology as that used in several published studies [18][19][20]24] by drawing a spherical 3 cm-VOI in the liver, a spherical 2 cm-VOI in the spleen, and four spherical 1.5 cm-VOI placed in the center of L1 to L4 (lumbar) vertebral bodies for BM. BM SUVmax was defined as the average of the maximum standardized uptake values of all vertebral bodies.…”
Section: Measurement Of Imaging Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations